Understanding strabismus - Irfan, Sameera (Jaypee Brothers Medical Publishers, 2014)
The subject of strabismus is like a vast ocean; standing by its shores, one cannot assess its full expanse but only by taking a deep plunge into it does one realize its true depth an dimension.